Enhanced fatigue lives in AA1050A/AA5005 laminated metal composites produced by accumulative roll bonding - Kümmel, Frank; Hausöl, Tina; Höppel, Heinz Werner; Göken, Mathias (Acta Materialia, 2016)
In this work laminated metal composites with alternating layers of commercial pure aluminum AA1050A and aluminum alloy AA5005 were produced by ARB. In order to vary the layer thickness and the number of interfaces different numbers of ARB cycles (4, 8 and 12) were applied. Subsequently, fatigue tests were performed and the related deformation and damage mechanisms were investigated. At high amplitudes crack growth occurs very straight through the whole sheet and is more or less unaffected by the interfaces of the individual layers in the composite. At lower amplitudes, where pronounced grain coarsening of the AA1050A layers occurs, the cracks deflect in front of the AA5005 layers and propagate in the coarsened AA1050A layers parallel to the bonding plane and the loading direction. Contrary to the composite, in both conventionally ARB processed AA1050A and AA5005 mono-material sheets grains are only locally coarsened around the crack tip and the fatigue cracks propagate very straight through the sheet width. Compared to AA1050A mono-material ARB sheets fatigue life and the cyclic stability are clearly enhanced in all composites. (C) 2016 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Accumulative roll bonding (ARB); Ultrafine-grained (UFG); Laminated metal composites (LMCs); Fatigue behavior; Dynamic grain coarsening